Stiffness characteristic of high temperature superconducting upper maglev system. (15th March 2022) - Wang, Li; Deng, Zigang; Kou, Long; Li, Haitao; Lei, Wuyang; Ke, Zhihao; Li, Qingshu
Highlights: Both the static experiment and the dynamic experiment were adopted to study the stiffness of the HTS upper maglev system. The result shows that levitation stiffness does not have a strong regular relation with the levitation height as prediction but has a linear relation with the levitation force in the limit space above the PMG. A systematic differential equation was proposed to describe the levitation stiffness characteristic of HTS upper Maglev. The proposed stiffness model can provide reference for the dynamic calculations of HTS Maglev vehicle system. Abstract: High temperature superconducting (HTS) magnetic levitation (maglev) train, by virtue of its passive stabilization, has the potential to become the next generation high-speed rail transit mode. For the further practical HTS maglev dynamic study and design, the levitation stiffness between the superconductors and the permanent magnet plays a significant role. Due to the nonlinear characteristics and the hysteresis phenomenon of the levitation force, the levitation stiffness is a variadic value. This varying stiffness complicates the vibration reduction design. And the violent vibrations caused by the lack of reasonable design can endanger the safety and comfort of the vehicle. In this paper, the levitation stiffness of a YBaCuO superconductor vessel levitating above a permanent magnetic guideway (PMG) in Halbach-array was measured and analyzed. First, a quasi-static experiment was designed to measure the levitation stiffness, which will be assessed during different vessel movement, separately. Subsequently, the natural frequencies of the levitation system under different working loads were measured by a series of dynamic experiments, and the levitation stiffness calculated by vibration was compared with the test result of the quasi-static experiment. Finally, a systematic differential equation was proposed to describe the levitation stiffness varying phenomena, and its dynamic characteristics were analyzed and verified by simulations as well. The result of this paper shows that the levitation stiffness does not have a strong regular relation with the levitation height as prediction but has a linear relation with the levitation force in the limit space above the PMG. And the studies about the stiffness characteristics with the proposed stiffness model in this paper can provide reference for engineering application and relative dynamic calculations.